The role of monoubiquitylation in the regulation of the transcription factor Elk-1 - Chow, Kam Yuen (2011)
Eukaryotic cells respond to extracellular stimuli by transmitting intracellular instructions via signalling pathways to coordinate appropriate responses. Mitogen-activated protein kinase (MAPK) pathways are often used to transmit these instructions to regulate gene expression, where Ternary Complex Factors (TCFs) are among their nuclear targets. Elk-1 is the founding member of the TCF family of transcription activators. The mechanism of function and regulation of Elk-1 has been extensively studied, therefore providing a paradigm for signal-induced transcription. The activity of Elk-1 is influenced by Post-Translational Modifications (PTMs), such as phosphorylation and sumoylation. Elk-1 ubiquitylation has also been reported in vitro, however little work has been done on this modification of Elk-1. This thesis sought to reveal the mechanism of regulation and function of Elk-1 ubiquitylation.